The Critical Role of Disulfide Bond Formation in Protein Sorting in the Endosperm of Rice - Kawagoe, Yasushi (American Society of Plant Biologists, 2005)
Many seed storage proteins, including monomeric 2S albumin and polymeric prolamin, contain conserved sequences in three separate regions, termed A, B, and C, which contain the consensus motifs LxxC, CCxQL, and PxxC, respectively. Protein-sorting mechanisms in rice (Oryza sativa) endosperm were studied with a green fluorescent protein (GFP) fused to different segments of rice α-globulin, a monomeric, ABC-containing storage protein. The whole ABC region together with GFP was efficiently transported to protein storage vacuoles (type II protein bodies [PB-II]) in the endosperm cells and sequestered in the matrix that surrounds the crystalloids. Peptide Gln-23 to Ser-43 in the A region was sufficient to guide GFP to PB-II. However, GFP fused with the AB or B region accumulated in prolamin protein bodies. Substitution mutations in the CCxQL motif in the B region significantly altered protein localization in the endosperm cells. Furthermore, protein extracts containing these substituted proteins had increased amounts of the endoplasmic reticulum (ER) chaperons BiP (for binding protein), protein disulfide isomerase, and calnexin as a part of protein complexes that were insoluble in a detergent buffer. These results suggest that the ER chaperons and disulfide bonds formed at the dicysteine residues in CCxQL play critical roles in sorting fused proteins in the endosperm cells.